2018
DOI: 10.1142/s0218348x18400170
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Characterization of Tight Oil Reservoir Pore Structure Using Nuclear Magnetic Resonance and Mercury Intrusion Porosimetry

Abstract: Tight oil sandstones have the characteristics of narrow pore throats, complex pore structures and strong heterogeneities. Using nuclear magnetic resonance (NMR) and mercury intrusion porosimetry (MIP), this paper presents an advanced fractal analysis of the pore structures and petrophysical properties of the tight oil sandstones from Yanchang Formation, Ordos Basin of China. Firstly, nine typical tight oil sandstone core samples were selected to conduct NMR and MIP test for pore structure characterization. Nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 28 publications
4
58
0
Order By: Relevance
“…According to the results of this work, a lower viscosity and lighter components of oil can facilitate the mass transfer process.Energies 2018, 11, 1495 2 of 20 methods for the quantitative determination of the gas (N 2 , CO 2 , CH 4 [28], C 2 H 6 , C 3 H 8 , or a mixture gas) diffusion coefficient in crude oil. These methods include the pressure decay method, X-ray computer-assisted tomography (CAT) method, magnetic resonance imaging (MRI) method [29,30], dynamic drop volume analysis (DPDVA), and pore-scale network modeling method. All of these methods have advantages and flaws:Direct testing method.…”
mentioning
confidence: 99%
“…According to the results of this work, a lower viscosity and lighter components of oil can facilitate the mass transfer process.Energies 2018, 11, 1495 2 of 20 methods for the quantitative determination of the gas (N 2 , CO 2 , CH 4 [28], C 2 H 6 , C 3 H 8 , or a mixture gas) diffusion coefficient in crude oil. These methods include the pressure decay method, X-ray computer-assisted tomography (CAT) method, magnetic resonance imaging (MRI) method [29,30], dynamic drop volume analysis (DPDVA), and pore-scale network modeling method. All of these methods have advantages and flaws:Direct testing method.…”
mentioning
confidence: 99%
“…However, the actual pore structures are more complex than those of the ideal formation. Several scholars have found that an exponential relationship, rather than a linear relationship, exists between the T2 spectrum (ms) and the pore radius (µ m) [23,27,42]: this finding is also supported by Figure 2b,c; the relationship can be expressed as follow:…”
Section: Combining Nmr and Hpmi Methodsmentioning
confidence: 53%
“…Thus, micron-scale pores remain difficult to describe [25,26]. High-pressure mercury injection (HPMI) is often integrated with NMR to reflect tight sandstone PSD [24,27], due to the resultant relatively full range of PSD characterization, although the relationship between T 2 spectrums and pore radii directly influences the accuracy of the NMR-HPMI-integrated PSD.…”
Section: Introductionmentioning
confidence: 99%
“…The core samples were collected from the outcrop of the tight sandstone formation. Tables 1 and 2 present the detailed oil and core sample properties used respectively. Energies 2018, 11,2667 3 of 17 mature standard reference in the experimental study of tight oil depletion in China, hence few reports on experimental evaluation have been published [51]. Therefore, further research needs to be done experimentally in order to fully grasp the factors affecting recovery of tight oil and how recovery factor can be improved significantly before a decision whether or not to exploit specific tight oil reservoir can be made.…”
Section: Methodsmentioning
confidence: 99%